Females Have Larger Ratio of Second‐to‐Fourth Digits Than Males in Four Species of Salamandridae, Caudata. Issue 8 (27th March 2015) - Kaczmarski, Mikołaj; Kubicka, Anna Maria; Tryjanowski, Piotr; Hromada, Martin
ABSTRACT Digit ratio (2D:4D) denotes the relative length of the second and fourth digits. It is considered to be a suitable biomarker of the in utero balance of fetal sex hormones, which affect early development of individuaĺs behavioral and morphological characteristics. In recent decades, digit ratio attracted a great attention in biology and psychology. However, for unmasking the biological basis of the phenomenon, extensive studies on non‐human animals are necessary. Despite it was hypothesized that digit ratio is well conserved in all Tetrapoda, and there exist studies on mammals, birds, and reptiles, there are only two such study on anuran amphibians. Therefore, the aim of this study is to investigate the 2D:4D in the most basal salamanders, Caudata. We have studied digit ratio in four species of newts: Triturus cristatus, Mesotriton alpestris, Lissotriton montandoni, and Lissotriton vulgaris, using museum collection. We used computerized measuring of each limbś photos. We have found out that, in M. alpestris, females 2D:4D of all four limbs were significantly larger than in males. In L. montandoni and L. vulgaris, only 2D:4D of rear limbs significantly differed, in females being larger. In T. cristatus, digit ratios of males and females did not statistically differ. Thus, the results confirmed our hypothesis that at least in M. alpestris, L. montandoni, and L. vulgaris, females seem to have larger 2D:4D comparing to males, the pattern known from most mammals and opposite to birds, reptiles and anuran amphibians. Anat Rec, 298:1424–1430, 2015. © 2015 Wiley Periodicals, Inc.